Recognition of Different Bird Category Using Image Processing - Rai, Bipin Kumar; Sharma, Shivani; Kumar, Gautam; Kishor, Kaushal (International Journal of Online and Biomedical Engineering (iJOE), 2022)
People like to do bird watching but to identify bird species they need help of Zoological Science. Bird watching gives health benefits which we get by enjoying nature. Species identification is a challenging task which may result in many different labels. Sometimes even experts may disagree on species. It is both difficult of humans and computers that hit the limit of visual abilities. Hence, to help the bird spectator, we have developed deep learning based algorithms using the concept of image processing that help in identifying bird species. It will recognize the input image by comparing the model with a trained model and then predict the bird species. All the details of the bird will be displayed as an output. Also, it will help us to create dataset if any image captured or uploaded by user is missing in dataset then user can add that image to dataset.